IMPROVING THE STUDENTS’ ACHIEVEMENT IN READING BY USING PRE-QUESTIONING - Janto, Muhammad Jupri Tri (Jurnal Bahasa Lingua Scientia, 2012)
This study was designed to improve the students? achievement in reading text by using Pre-Questioning. It was conducted in order to find model of teaching and learning that occurs, especially, in reading class. In this application, this study was done in cycles involved planning the action, implementing action, observing, and reflecting which we implemented in two cycles. Thus, this study was directed to solve practical problem in reading ability especially the student?s lack of vocabulary and understanding text in the process of teaching and learning. The research was intended to know how Pre-Questioning before reading can be used to improve students achievement in reading text at second year students of MTsN Bandung, Tulungagung in academic year 2011/2012.